Fluorescent organo-antimony compounds as precursors for syntheses of redox-active trimeric and dimeric alkali metal antimonides: an insight into electron transfer reduction processes. Issue 5 (13th January 2022) - Nag, Ekta; Kulkarni, Aditya; Gorantla, Sai Manoj N. V. T.; Graw, Nico; Francis, Maria; Herbst-Irmer, Regine; Stalke, Dietmar; Roesky, Herbert W.; Mondal, Kartik Chandra; Roy, Sudipta
Abstract : Fluorescent diarylchlorostibane, distibane are utilized as precursors for syntheses of redox-active dimeric/trimeric alkali-metal antimonides by reductive dehalogenation. DFT and EDA-NOCV analysis are performed to shed light on the electron transfer mechanism. Abstract : (Tip)2 SbCl (1, Tip = 2, 4, 6-triisopropylphenyl) has been utilized as a precursor for the synthesis of the distibane (Tip)4 Sb2 (4 ) via one-electron reduction using KC8 . The two-electron reduction of 1 and 4 afforded the novel trinuclear antimonide cluster [K3 ((Tip)2 Sb)3 (THF)5 ] (6 ). Changing the reducing agent from KC8 to a different alkali metal resulted in the solid-state isolation of corresponding stable dimeric alkali metal antimonides with the general formula [M2 ((Tip)2 Sb)2 (THF) p − x (tol) x ] (M = Li (14 ), Na (15 ), Cs (16 )). In this report, different aspects of the various reducing agents [K metal, KC8, and [K2 (Naph)2 (THF)]] used have been studied, correlating the experimental observations with previous reports. Additional reactivity studies involving 1 and AgNTf2 (Tf = trifluoromethanesulfonyl) afforded the corresponding antimony cation (Tip)2 Sb + NTf2 − (19 ). The Lewis acidic character of 19 has been unambiguously proved via treatment with Lewis bases to produce the corresponding adducts 20 and 21 . Interestingly, the precursors 1 and 4 have been observed to be highly luminescent, emitting green light under short-wavelength UV radiation. All the reported compounds have been characterized via NMR, UV-vis, mass spectrometry, and single-crystal X-ray diffraction analysis. Cyclic voltammetry (CV) studies of 1 in THF showed possible two electron reduction, suggesting the in situ generation of the corresponding radical-anion intermediate 1˙ − and its subsequent conversion to the monomeric intermediate (Tip)2 Sb − (5 ) upon further reduction. 5 undergoes oligomerization in the solid state to produce 6 . The existence of 1˙ − was proved using electron paramagnetic resonance (EPR) spectroscopy in solution. CV studies of 6 suggested its potential application as a reducing agent, which was further proved via the conversion of Tip–PCl2 to trimeric (Tip)3 P3 (17 ), and cAACP–Cl (cAAC = cyclic alkyl(amino)carbene) to (cAAC)2 P2 (18 ) and 4, utilizing 6 as a stoichiometric reducing agent.